2021
DOI: 10.3390/diagnostics11081508
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Analysis of In Vivo Hyperspectral Images for Automated Intraoperative Nerve Detection

Abstract: Nerves are critical structures that may be difficult to recognize during surgery. Inadvertent nerve injuries can have catastrophic consequences for the patient and lead to life-long pain and a reduced quality of life. Hyperspectral imaging (HSI) is a non-invasive technique combining photography with spectroscopy, allowing non-invasive intraoperative biological tissue property quantification. We show, for the first time, that HSI combined with deep learning allows nerves and other tissue types to be automatical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 55 publications
(72 reference statements)
1
20
0
Order By: Relevance
“…To compute statistically significant differences, a two-tailed paired t-test (p = 0.05) similar to previous works in HSI classification analysis using Excel (Microsoft Office 365, Microsoft, Redmond, WA, USA), was used 37 .…”
Section: Methodsmentioning
confidence: 99%
“…To compute statistically significant differences, a two-tailed paired t-test (p = 0.05) similar to previous works in HSI classification analysis using Excel (Microsoft Office 365, Microsoft, Redmond, WA, USA), was used 37 .…”
Section: Methodsmentioning
confidence: 99%
“…Based on a previous animal study from Barberio et al comparing the two most successful deep learning models, i.e., support vector machines (SVMs) [ 52 , 53 , 54 ] and CNNs for HSI tissue segmentation, the CNN model achieved an overall higher sensitivity for all tissue classes (89.4%) except for the nerve class, which had a sensitivity of 76.3% [ 46 ]. Consequently, this combined with deep learning allowed for the automatic discrimination of six different tissue classes (artery, vein, adipose, muscle, skin, and nerve), supporting our decision to adopt the CNN model in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Using a four-layer neural network, Boris Jansen-Winkeln et al achieved an 86% sensitivity and a 95% specificity in identifying colorectal cancer (CRC) [ 45 ]. Barberio et al showed that HSI combined with CNNs could be used to automatically recognize key anatomical structures such as blood vessels and nerves [ 46 ]. Collins and Maktabi [ 47 ] showed that colorectal and esophagogastric cancer could also be detected with various machine learning models, and CNNs often produced the best results.…”
Section: Introductionmentioning
confidence: 99%
“…However, the accuracy of the automatic detection was rather low to be acceptable within a clinical setting. For that reason, another study was performed [34] focusing on automatic tissue recognition in animals. During neck dissections in several pigs, in vivo HSI acquisitions were made, and different tissue classes (such as muscle, nerve, vessels, skin, etc.)…”
Section: Recognition Of Anatomical Structuresmentioning
confidence: 99%